Women, Work and Computerization 2000
DOI: 10.1007/978-0-387-35509-2_2
|View full text |Cite
|
Sign up to set email alerts
|

Making the Computer Masculine

Abstract: Abstract:The new field of computer occupations has acquired a masculine character in a very short time, even in a period in which women's participation in the labour market increased significantly. In this article, I want to show how the computer on symbolic level became inextricably bound up with prevailing masculine values as early as the '50s and '60s. The empirical material is based on an analysis of newspaper articles on computers from this period. I will argue that the brain metaphor played an important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…This design practice is not confined to history. Even today we see similar patterns, as exemplified by the design of the interfaces of the first computers and other digital information systems which were attuned to the experience of technically skilled users (Lie, 1996;Oost, 2000;Oudshoorn et al, in preparation;Rommes et al, 1999).…”
Section: The Gender Scripts Of Shavers Bicycles and Microwavesmentioning
confidence: 95%
See 1 more Smart Citation
“…This design practice is not confined to history. Even today we see similar patterns, as exemplified by the design of the interfaces of the first computers and other digital information systems which were attuned to the experience of technically skilled users (Lie, 1996;Oost, 2000;Oudshoorn et al, in preparation;Rommes et al, 1999).…”
Section: The Gender Scripts Of Shavers Bicycles and Microwavesmentioning
confidence: 95%
“…We suggest that artifacts are actually ''gendered by design'' (Green, Owen, & Pain, 1993). In the last decades, feminist scholars, including ourselves, have shown how objects embody traits designed with gender in mind (Berg & Lie, 1993;Cockburn & Dillic, 1994;Cockburn & Ormrod, 1993;Gill & Grint, 1995;Horowitz & Mohun, 1998;Kirkham, 1996;Lie, 1996;Oost, 1995Oost, , 2000Oudshoorn, 1996;Rommes, Oost, & Oudshoorn, 1999;Rothschild, 1999;Wajcman, 1991). Feminists have shown how gender is further imprinted onto objects through instructions, advertisements, associa-tions with gendered divisions of labor, and associations with gender symbols and myths (Hubak, 1996;Lie & Sørenson, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the concept of "gender scripts" explains how gendered relations and identities are inscribed into the design of technology. Design decisions and procedures influence user representations, consumption, technological frames and domestication by steering users to perform according to gendered norms (Oost 2000(Oost , 2003Oudshoorn et al 2004;Rommes et al 1999;Rommes 2002). These scripts can be negotiated and contested but they have the power to sustain prevailing gender disparities.…”
Section: Gender Scripts and Domesticationmentioning
confidence: 99%
“…For instance, studies of 1990s home computers found that men tended to relate to the new technology as a complex, auspicious tool and an opportunity to express masculinity. Women, however, tended to view it as part of routine office work (Haddon 2006;Oost 2000). Emphasising the agency involved in decisions to purchase and absorb technologies into home routines, domestication theory explains how context of use acquires gendered connotations (Lie 1995Oost 2000.…”
Section: Gender Scripts and Domesticationmentioning
confidence: 99%
See 1 more Smart Citation